Exotic Epiphytes on Tree Ferns in Cibodas Botanical Gardens: The Importance of Light Preferences and Host Characteristics - Junaedi, Decky Indrawan; Nasution, Taufikurrahman (Journal of Tropical Life Science, 2018)
The study of exotic epiphytes on tree ferns is relatively scarce. Biological invasion of exotic epiphytes may imply negative consequences to native epiphytes and tree ferns, which are important components in tropical mountainous rainforest ecosystems. This study surveyed exotic epiphytes on tree ferns in Cibodas Botanical Gardens (CBG) and adjacent forests next to CBG. The objectives of this study are: a) to conduct inventory study of exotic epiphyte species on tree ferns, b) to examine how different these exotic epiphytes from each other based on their micro-climate preferences, c) to conduct invasive risk assessment of those exotic epiphytes, and d) to model the effect of environmental factors and host (tree ferns) characteristics to the occurrence of exotic epiphytes on tree ferns. We conducted multi-dimensional analysis to examine how different these exotic epiphytes based on their micro-climate parameters. We used Weed Risk Assessment (WRA) framework to estimate the invasion risks of surveyed exotic epiphytes. We performed Bayesian logistic regression to test the correlation between environmental and host characteristics and the occurrence probability of exotics epiphytes on tree ferns. We found 13 exotic epiphyte species on two native tree ferns species (Cyathea junghuhniana and Cyathea contaminans). Multidimensional analysis showed that Axonopus compressus is very different from other exotic epiphytes due to its environmental preferences. Ageratina riparia and Clidemia hirta were exotic epiphytes with the highest invasion risks. Therefore, we suggested that A. riparia and C. hirta are more likely to become invasive and may contribute significant impacts to native ecosystems. Lastly, the presence of Austroeupatorium inulaefolium as exotic epiphytes in tree ferns negatively correlated with the host height. Further study is needed to incorporate biological traits of the exotic epiphytes and more specific environmental parameters such as light chromatic quality in to the exotic epiphyte occurrence model. This study provides evidence for the existences of exotic epiphytes on tree ferns. The result of this study may also indicate that host characteristics and micro-climate factors could play important roles to inhibit the occurrence of exotic epiphytes on tree ferns.